Preparation of [C60]Fullerene Nanowhisker-gold Nanoparticle Composites and Reduction of 4-Nitrophenol through Catalysis - Jeong Won Ko; Jiulong Li; Weon Bae Ko (Nanomaterials and Nanotechnology)
A gold nanoparticle solution was prepared by adding sodium borohydride (NaBH4), trisodium citrate dihydrate (C6H5Na3O7⋅2H2O), cetyltrimethyl ammonium bromide (CTAB,(C16H33)N(CH3)3Br), ascorbic acid (C6H8O6), and potassium tetrachloroaurate(III)(KAuCl4) to distilled water and stirring the solution for 15 min. [C60]fullerene nano‐ whisker-gold nanoparticle composites were synthesized using C60-saturated toluene, the gold nanoparticle solution, and isopropyl alcohol by liquid-liquid interfacial precipi‐ tation (LLIP). The product of the nanocomposites was characterized by X-ray diffraction, scanning electron microscopy, Raman spectroscopy, transmission electron microscopy, and solid- state 13C-nuclear magnetic resonance spectroscopy. The catalytic activity of the [C60]fullerene nanowhisker-gold nanoparticle composites was confirmed in 4-nitrophenol reduction by UV-vis spectroscopy.